Investigating inspirational leader communication in an elite team sport context - Smith, M. J.; Figgins, S. G.; Jewiss, M.; Kearney, P. E. (International Journal of Sports Science & Coaching, 2018)
The purpose of this study was to examine how leader communication inspires athletes in a team sport context. Footage of elite rugby coaches and athlete leaders delivering genuine speeches were used as a stimulus. Team sport athletes (n?=?20) watched this footage and identified which aspects of the communication inspired them. Follow-up interviews were conducted to explore what the participants were inspired by and why. Thematic analyses revealed six main dimensions of what was inspiring within the content of the speech, including showing how the team can be successful, embracing and reinforcing the underdog status, and creating pride and unity within the team. In addition, a number of features of effective delivery were identified, including the tone of voice, fluency of speech, and the way key ideas were emphasised.